Assessing the impact of pesticides: An overview - Jawale CA; Rajput KH; Ugale BJ (International Journal of Life Sciences, 2017)
There are three types of pesticides. They are organochlorine, organophosphate and carbomate compounds. Organophosphorus compounds are remarkable for their selective toxicity, low persistence and greater biodegradability. Organophosphates are less lipophilic than chlorinated hydrocarbons. Because of the rapid biodegradability, the organophosphate insecticides have replaced more persistent organochlorine compounds and are used in greater quantity. India accounts for one third of pesticides poisoning case in the world. A majority of them get exposed for long periods cases of blindness, cancer, deformities, diseases of liver and nervous system etc., from pesticide poisoning have been identified. These pesticides however have a large scale of contamination in the ecosystem as a result of which they cause various effects on the biotic components of the environments besides the pests or targets species for which the chemical is applied. The pesticide across media indicates portals of entry into the existing food web. The basic principle of adsorption, distribution, metabolism and excretion all toxicology is equally important when assessing toxic effects of pesticides on animal life. Various animals have also been used as indicators to measure the extent of pesticide pollution of the environment. The present investigations are attention is given mostly to studies pesticide effects on animal life and the environments.